Socio-cultural competence in modern educational paradigm - Kseniya O. Kuzovenkova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article analyzes the development dimension of social competence in the modern educational environment. "Socio-cultural competence" Approaches to understanding the essence of the concept. The mechanism of the formation of social and cultural thinking concerning personal characteristics and individual preferences. The analysis of the work of the scientific community on the relevance of social competence in the teaching environment. There is a number of positions, which causes difficulty in the effective implementation of the socio-cultural competence, based on the level of pedagogical skills. Obtained basic aspects of social competence in the socio-cultural information space system. Revealed general pedagogical techniques that promote the formation of social competence. A number of reference principles of social competence in the teaching environment.